Kearifan Lokal Pendidikan Pesantren Tradisional di Jawa: Kajian atas Praktek Penerjemahan Jenggotan - Irhamni Irhamni (Ulumuna, 2011)
The pesantren institution is unique in education practice so it’s one of distinguished subsystem in national education system. This article focused on study of jenggotan translation practiced in course of traditional pesantren in Java. Locus of the study is in Pesantren Gondanglegi, Malang practicing jenggotan practice. The approach used is qualitative research employing the grounded research model. This study concludes that practices of jenggotan translation lay on two fundamental values. The first is the kepesantrenan value and the second is intelectual-academic one.